Risk of infectious mononucleosis is not associated with prior infection morbidity - Rostgaard, Klaus; Kristjánsson, Ragnar; Davidsson, Olafur; Biel-Nielsen Dietz, Jojo; Søegaard, Signe Holst; Stensballe, Lone Graff; Hjalgrim, Henrik (Frontiers in Epidemiology, 2025)
BackgroundThe probability of presenting with infectious mononucleosis (IM) upon primary Epstein–Barr virus infection increases dramatically at the start of puberty. Aiming to understand why that is, we assessed whether the number of infection-related health events during two specific time periods−ages 10–12 years (pre-teen window) and the three most recent years (recent window)−could predict the likelihood of individuals aged 13–19 years developing IM.MethodsWe used sibship-stratified Cox regression to mitigate socio-demographic confounding and bias. Consequently, we only followed members of IM-affected sibships aged 13–19 years between 1999 and 2021 for IM, based on information from complete nationwide Danish administrative and health registers. Estimates were further adjusted for sex, age, birth order (1, 2, 3+) and sibship constellation [number of siblings and their signed (older/younger) age difference to the index person]. Infection-related health events defining the exposures considered were either a category of antimicrobial prescription, or a hospital contact with an infectious disease diagnosis. We measured evidence/probability of the associations using asymptotic Bayes factors, rather than using p-value based testing.ResultsThe adjusted hazard ratio (HR) for IM with 95% confidence limits for an additional antimicrobial prescription in the pre-teen exposure window was [1.01; 0.98–1.04], and the corresponding adjusted HR for an additional antimicrobial prescription in the recent exposure window was [1.02; 0.99–1.06].ConclusionsIM was not preceded by unusual numbers of infections. Small effect sizes, together with small variation in exposure, did not render the assessed exposures useful for predicting IM for public health or the clinic.